2006
DOI: 10.1111/j.1460-9568.2006.05072.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to silent lipreading in normal hearing male and female subjects

Abstract: In the past, researchers investigated silent lipreading in normal hearing subjects with functional neuroimaging tools and showed how the brain processes visual stimuli that are normally accompanied by an auditory counterpart. Previously, we showed activation differences between males and females in primary auditory cortex during silent lipreading, i.e. only the female group significantly activated the primary auditory region during lipreading. Here we report and discuss the overall activation pattern in males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
(114 reference statements)
4
21
0
Order By: Relevance
“…Males, on the other hand, only activated secondary auditory areas, which might indicate that they rely less on the auditory counterpart of the visible speech image than females. This hypothesis is supported by previously reported sex differences in other brain regions during lipreading [Ruytjens et al, 2006]. It was found that females have more activation in multimodal inferior parietal, inferior frontal, precentral and angular regions, suggesting that females associate the lip movements with the absent speech sound and mirror the moving lips.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Males, on the other hand, only activated secondary auditory areas, which might indicate that they rely less on the auditory counterpart of the visible speech image than females. This hypothesis is supported by previously reported sex differences in other brain regions during lipreading [Ruytjens et al, 2006]. It was found that females have more activation in multimodal inferior parietal, inferior frontal, precentral and angular regions, suggesting that females associate the lip movements with the absent speech sound and mirror the moving lips.…”
Section: Discussionsupporting
confidence: 79%
“…These results, together with previously reported sex differences in activation during lipreading [Ruytjens et al, 2006], suggest that a different neural network is involved in lipreading in the two sexes. Both groups scored high on the test and this indicates that neither pattern of activity is superior to the other in terms of performance in the present lipreading task.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, when women are visually learning novel pseudowords, they bilaterally activate their so-called visual word form area; men primarily activate just the left visual word form area (Chen et al, 2007;Dong et al, 2008). Finally, Ruytjens, Albers, van Dijk, Wit, and Willemsen (2006) reported that men when speech-reading numbers activated a more left-lateralized set of networks than women.…”
Section: Discussionmentioning
confidence: 95%
“…Primary sensory fields may even achieve multisensory status as a function of associative learning. For example, primary auditory cortex in humans is responsive to specific silent visual scenes of speech (Ruytjens, Albers, van Dijk, Wit, & Willemsen, 2006) and there is multisensory integration of faces and voices in A1 of rhesus monkeys (Ghazanfar, Maier, Hoffman, & Logothetis, 2005). Multisensory integration in A1 can be formed during learning (Brosch, Selezneva, & Scheich, 2005) and in subsequent memory effects of multimodal sensory pre-conditioning (Headley & Weinberger, 2015).…”
Section: Discussionmentioning
confidence: 99%